2006
DOI: 10.1108/17466660200600028
|View full text |Cite
|
Sign up to set email alerts
|

The impact on parenting and the home environment of early support to mothers with new babies

Abstract: The study reported here aimed to evaluate the impact on parenting and the home environment of community volunteer home visiting offered during or soon after pregnancy to potentially vulnerable mothers. A cluster‐randomised study allocated Home‐Start schemes to intervention or comparison (existing services) conditions. Mothers were screened at routine health checks. Families in intervention and comparison areas were assessed at two and 12 months. The results showed that comparing families receiving support and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Barnes, Senior & MacPherson (2009) found no effects of postnatally offered Home-Start on maternal depression at two and 12 months of age of the baby's in a study with three groups: a Home-Start supported group, case-matched controls and mothers offered, but not receiving support. In an additional report on this study Barnes, MacPherson and Senior (2006) found a greater reduction in parent-child relationship difficulties for supported families compared the casematched controls, but mothers of the Home-Start group offered their children fewer healthy foods.…”
mentioning
confidence: 99%
“…Barnes, Senior & MacPherson (2009) found no effects of postnatally offered Home-Start on maternal depression at two and 12 months of age of the baby's in a study with three groups: a Home-Start supported group, case-matched controls and mothers offered, but not receiving support. In an additional report on this study Barnes, MacPherson and Senior (2006) found a greater reduction in parent-child relationship difficulties for supported families compared the casematched controls, but mothers of the Home-Start group offered their children fewer healthy foods.…”
mentioning
confidence: 99%
“…Recognising that vulnerable women may be 'hard-toreach' for maternity services, in 2010 the National Institute for Health and Care Excellence (NICE) recommended research into the effectiveness of third sector family support on improving outcomes for mothers and babies (National Institute for Health and Care Excellence, 2010). Although volunteer breastfeeding peer support schemes (Dykes, 2005;Muller et al, 2009) and schemes that provide volunteer social and mentoring support to new mothers (Barnes, 2006;Suppiah, 2008) are well established in England, volunteer support for pregnant women is underdeveloped. There has been recent interest from funders in testing volunteer support for disadvantaged pregnant women, with pilot schemes including peer supporters for pregnancy and early parenthood (Bhavani et al, 2015), and volunteer support to improve mothers' mental health (Barlow and Coe, 2012).…”
mentioning
confidence: 99%
“…However, it may be that this indirect approach is not sufficiently powerful to make significant changes in caregivers' involvement with their children on a routine basis at home. Barnes et al (2006) arrived at a similar conclusion after a large-scale evaluation of Home-Start, an international home visiting program which connects parents to parents. Centered in England, this study did not find significant changes on most maternal and child outcomes following one year of participation in home visiting services.…”
Section: Discussionmentioning
confidence: 53%
“…Over the past decade the United Kingdom initiated a national system of early childhood education (Carpenter and Campbell 2008). Yet, the evaluations of the two-generational, early childhood intervention programs which have recently emerged (e.g., Sure Start and Home-Start) show similar findings regarding the achievement of child outcomes as well as the need to integrate evidence-based practice (Barnes et al 2006;National Evaluation of Sure Start 2006). With the current Obama administration's prioritization of home visiting in the US, and the growing emphasis on family-focused early childhood in the international community, now is the time to direct our empirical efforts to enhancing home-based services for children who live in socioeconomic disadvantage.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation